Title -The Celluloid universe of Jahnu Barua : An analytical study of select flims - Jubilee Saikia Marangi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Cinema is considered to be the most powerful mass media in the contemporary times. Cinema, with its innovative ways of storytelling and proliferatingmessage, has been changing the ways people think about the life and the world in a very impactful manner .The process of evaluation or analysis of films is also as ancient as the medium itself.Cinema is known as the seventh form of Art .The history of Assamese Cinema started with the movie Joymoti, which was produced and directed by Jyotiprasad Agarwalla.Pioneering figures of the erstwhile Assamese cultural world like Lakshminath BezBaruah,Umesh Barua, Rajanikanta Bordoloi offered their own views about the film. But Assamese cinema, in true sense of the term, gained its real momentum only during the eighties. A good number of filmmakers offered a good number of powerful and entertaining Assamese films in this time.Jahnu Baruahalso introduced himself as a sensitive and committed filmmaker during this decade. Tillnow, JahnuBaruah has directed a total number of fifteen films, both in Assamese and Hindi Language. The films of Jahnu Baruah stand for his brilliant hold over the medium as well as his hold over the technical and artistic craftsmanship .A movie can be an entertainer as wells an educator. The movies of Baruah very convincingly carry forward those entertaining and educational elements in a minutely crafted aesthetic manner. This paper attempts an analytical discussion of two of the films of Jahnu Baruah-Haladhiya Saraye Baodhan Khay (1987) and Baandhon (2012) .The paper will also deal with some of the cinematic techniques of Baruah as a filmmaker.